Employed Vocational Rehabilitation Applicants with Visual Disabilities: Factors Associated with Timely Service Delivery. (January 2020) - Crudden, Adele; Sui, Zhen; Lund, Emily
Introduction: Employed applicants for vocational rehabilitation need timely services to improve the likelihood of their successful job retention or career advancement. Little research exists that examines timeliness of services among employed applicants, particularly for applicants with visual disabilities. This study investigated time from vocational rehabilitation application to a signed Individualized Plan for Emplolyment (IPE) for employed applicants with visual disabilities. Method: The sample of 5, 096 competitively employed vocational rehabilitation applicants from the FY2015 RSA-911 report was combined with survey responses from 51 vocational rehabilitation agencies about services to persons with visual disabilities. Multilevel modeling was used to examine effects of state-level and individual-level characteristics and cross-level interactions on the length of waiting time from vocational rehabilitation application to signed IPE. Results: The time from application to IPE was shorter for employed applicants with visual disabilities who received services from separate vocational rehabilitation agencies compared to that of combined vocational rehabilitation agencies. Employed vocational rehabilitation applicants with visual disabilities waited longer if they were younger, non-White, or received disability benefits. Official job-retention policies in state vocational rehabilitation agencies appeared to reduce the delay of IPE implementation for persons with secondary disabilities, for applicants who received disability benefits, and for persons who worked more hours per week. Discussion: Additional research to determine how vocational rehabilitation can provide services to employed persons as soon as possible after application is indicated, particularly for persons applying to combined agencies. Implications for practitioners: Vocational rehabilitation providers should explore ways to expedite service delivery, particularly for persons who are younger, non-White, or receiving disability benefits. Implementing official vocational rehabilitation policies for addressing job-retention and career-advancement cases may be one avenue to expedite services to some employed applicants.